The Benefits Seen with Mechanical Thrombectomy for Anterior Circulation Ischemic Stroke are Independent of Occlusion Location. (16th November 2020) - Chagoya, Gustavo; Thaci, Bart; Elsayed, Galal; Salehani, Arsalaan; Pope, Brandon; Gupta, Saksham; Bernstock, Joshua; Harrigan, Mark R
Abstract: INTRODUCTION: Intra-arterial thrombectomy (IAT) is the standard of care treatment for acute ischemic stroke (AIS) secondary to large vessel occlusion (LVO). METHODS: A retrospective chart review was conducted on all consecutive adult (age >18 years) patients undergoing IAT at a single comprehensive stroke center between 2014 and 2017. Decision-making criteria for intervention were based on ASPECTS, onset of symptoms (<6 hrs), and arrival NIHSS in accordance to the accepted standard of care. Ordinary least squares (OLS) multiple linear regression analysis was performed on continuous outcome and categorical independent variables. Statistical analyses including descriptive statistics were performed using R (RStudio 1.2.1335). RESULTS: A total of 168 patients underwent IAT and were included in the study. Cohort demographics revealed a mean age of 64.0 ± 13.4 years, with 54.2% being female, 60.7% Caucasian, and 33.9% African-American. Pre-existing comorbidities and risk factors included tobacco use (52.4%), a-fib (21.4%), diabetes (18.5%), hypertension (56.5%), and hyperlipidemia (30.4%). Average systolic blood pressure on admission was 144 ± 27.6 mmHg. The majority of large vessel occlusions occurred at the M1 (40.5%), carotid terminus (20.8%), ICA (20.2%), and M2 (13.7%) segments. ACA and CCA occlusions were rare, accounting for 2.4% each. Mean mRS on admission and at 90 days post-thrombectomy were 3.99 ± 0.951 and 4.58 ± 2.08, respectively. OLS regression revealed a weak association between M1 occlusions and higher mRS at 90 days (coefficient 2.27, [CI] 0.19-4.34; P < . 05) that was not seen with any other occlusion site. CONCLUSION: Thrombectomy outcomes appear to be independent of the site of occlusion, although a weak association between M1 occlusions and higher post-thrombectomy mRS at 90 days needs further evaluation in future, larger cohort studies.